Реабилитация студентов средствами лечебной физической культуры - Давлетьярова К. В. Ксения Валентиновна; Капилевич Л. В. Леонид Владимирович; Солтанова В. Л. Виктория Леонидовна; Баранова Е. А.; Андреев В. И. Владимир Игоревич (2011, 2011)
В фонде НТБ ТПУ отсутствует